2022
DOI: 10.7759/cureus.24118
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health-Related Quality of Life of Epilepsy Patients in Jeddah, Saudi Arabia

Abstract: BackgroundEpilepsy puts an enormous burden on the physical and mental health of patients and can negatively impact their Health-Related Quality of Life (HRQoL). Previous studies have identified multiple factors impacting patients' HRQoL; however, a consensus has not been reached, as these factors vary among different populations. This has not been sufficiently investigated in Saudi Arabia. Thus, this study aims to assess the HRQoL of epilepsy patients, as measured by the Quality Of Life In Epilepsy-31 (QOLIE-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The participants’ mean QOLIE overall score was 65.17±19.1, which is slightly higher than the overall score reported in a similar study in Jeddah. 36 Significant associations were observed between the following: gender and energy/fatigue, medication effect, social function, and QOLIE overall score. The association between gender and energy/fatigue is in line with the study by Tayeb et al, 36 in which female PWE demonstrated relatively lower energy scores than male PWE.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The participants’ mean QOLIE overall score was 65.17±19.1, which is slightly higher than the overall score reported in a similar study in Jeddah. 36 Significant associations were observed between the following: gender and energy/fatigue, medication effect, social function, and QOLIE overall score. The association between gender and energy/fatigue is in line with the study by Tayeb et al, 36 in which female PWE demonstrated relatively lower energy scores than male PWE.…”
Section: Discussionmentioning
confidence: 94%
“… 36 Significant associations were observed between the following: gender and energy/fatigue, medication effect, social function, and QOLIE overall score. The association between gender and energy/fatigue is in line with the study by Tayeb et al, 36 in which female PWE demonstrated relatively lower energy scores than male PWE. Meanwhile, the association between gender and medication effect can be substantiated by the study conducted by Reddy (2017).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Treatment response may be partial, manifesting as a reduction of seizures or cessation of some but not all of the seizure types 36,37 . Although seizure freedom is the ultimate treatment goal in patient care, when this is not feasible, control of selected seizure types, prevention of prolonged seizure activity (status epilepticus), or the reduction in seizure frequency can have a relevant impact on quality of life and seizure‐associated risks 38–40 . The partial treatment response may also help select more effective combination treatments or develop optimized therapies.…”
Section: The Clinical Complexity Of Drug‐resistant Epilepsymentioning
confidence: 99%
“…36,37 Although seizure freedom is the ultimate treatment goal in patient care, when this is not feasible, control of selected seizure types, prevention of prolonged seizure activity (status epilepticus), or the reduction in seizure frequency can have a relevant impact on quality of life and seizure-associated risks. [38][39][40] The partial treatment response may also help select more effective combination treatments or develop optimized therapies. DRE may not result from one mechanism only, as multiple mechanisms can contribute to drug resistance.…”
Section: The Clinical Complexity Of Drug-resistant Epilepsymentioning
confidence: 99%